2017
DOI: 10.1590/s0100-83582017350100038
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATING YIELD LOSSES AND ECONOMIC THRESHOLD LEVEL OF Parthenium hysterophorus IN FORAGE SORGHUM

Abstract: ) on the yield and yield components of forage sorghum along with parthenium economic threshold level. The experiment was laid out during the summer in a randomized complete block design with four replications. Different parthenium densities reduced yield and yield components of forage sorghum, as the parthenium density increased significant decline in yield and yield components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Data on stem diameter averaged over both the years showed that S.S. hybrid plants obtained highest stem diameter (1.85cm) in the experimental unit where minimum weed density (1.63 weeds tiller m -2 ) was observed and minimum stem diameter (1.0875 cm) was observed at highest weed intensity (410.62 tillers m -2 ) (Tables 1 and 3). These findings are in concurrent with the conclusions of Asif et al, 2017 andGholami et al, 2013 who observed that stem diameter reduced in un weeding treatment as compare to other weeding treatments, which shows minimum weed intensity.…”
Section: Number Of Leaves Per Tillersupporting
confidence: 89%
“…Data on stem diameter averaged over both the years showed that S.S. hybrid plants obtained highest stem diameter (1.85cm) in the experimental unit where minimum weed density (1.63 weeds tiller m -2 ) was observed and minimum stem diameter (1.0875 cm) was observed at highest weed intensity (410.62 tillers m -2 ) (Tables 1 and 3). These findings are in concurrent with the conclusions of Asif et al, 2017 andGholami et al, 2013 who observed that stem diameter reduced in un weeding treatment as compare to other weeding treatments, which shows minimum weed intensity.…”
Section: Number Of Leaves Per Tillersupporting
confidence: 89%
“…Similar negative effects have been reported on the number of grains per cob, 1000-grain weight and yield of maize enduring Parthenium weed competition for 5-8 weeks (Safdar et al, 2016). In a recent study, sorghum crop grown for fodder purpose suffered from severe losses in plant height, stem diameter, leaf area and yield by Parthenium weed competition at the weed density of 16 plants m −2 (Asif et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…This, we suspect is mainly due to severe resource competition at the higher weed densities and longer competition durations. Previous studies on other cereal crops also showed that this weed caused substantial yield losses at relatively high densities and for longer competition durations (Asif et al, 2017;Bajwa et al, 2019c,d;Safdar et al, 2015Safdar et al, , 2016Tamado et al, 2002). Most weed species at high densities often increase inter-specific competition which benefit them by physical dominance and better resources acquisition and crop suppression depends on weed density also differ among weed species.…”
Section: Discussionmentioning
confidence: 90%
“…In another study on maize, dry biomass of parthenium weed increased over 400% as the weed density increased from 5 to 20 plants m -2 (Safdar et al, 2015). Furthermore, parthenium weed is known to uptake more nutrients from root zone at higher densities (Asif et al, 2017;Safdar et al, 2015), enabling the whole population to grow faster and affect the crop growth at these high densities.…”
Section: Discussionmentioning
confidence: 99%